2017
DOI: 10.3390/nu9121345
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyphenol-Rich Interventions on Cardiovascular Risk Factors in Haemodialysis: A Systematic Review and Meta-Analysis

Abstract: End-stage kidney disease is a strong risk factor for cardiovascular-specific mortality. Polyphenol-rich interventions may attenuate cardiovascular disease risk factors; however, this has not been systematically evaluated in the hemodialysis population. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the following databases were searched: Cochrane Library (), MEDLINE (), Embase (), and CINAHL (). Meta-analyses were conducted for measures of lipid profile, inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…As discussed in our previous review, (Marx et al 2017) clinical trials involving polyphenol interventions should implement measures to control for background polyphenol intake, as this may influence study results. Most studies in our review provided dietary advice to control for this, although there was no discussion regarding adherence to this advice.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in our previous review, (Marx et al 2017) clinical trials involving polyphenol interventions should implement measures to control for background polyphenol intake, as this may influence study results. Most studies in our review provided dietary advice to control for this, although there was no discussion regarding adherence to this advice.…”
Section: Discussionmentioning
confidence: 99%
“…struggled to identify effects of polyphenols in humans. However, a recent meta-analysis based on ten human intervention studies reported that different polyphenol-based interventions in humans were found to significantly reduce diastolic blood pressure and triglyceride levels (Marx et al, 2017), while inconclusive effects on systemic pro-inflammatory markers (CRP and IL-6) as well as oxidative stress markers, except for myeloperoxidase, were found. Based on this combined analysis,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite individual studies indicating signi cant improvements, pooled results depicted no effect for most outcomes excepting myeloperoxidase, diastolic blood pressure, and triglycerides (29). Only myeloperoxidase, a measure of oxidative stress, had a large pooled effect size (29).…”
Section: Discussionmentioning
confidence: 94%
“…The results of another study by Cynthia et al contradicted the previous evidence, mostly attributed to the intervention of multifactorial treatments received by the diabetic participants along with the green tee polyphenols. In this sense, a meta-analysis endorsed the preliminary support of polyphenol-rich interventions in the improvement of cardiovascular risk factors among hemodialysis patients (29).…”
Section: Discussionmentioning
confidence: 99%